Educational potential of subject training of the future teacher in the conditions of modern educational policy - Allagulov, Arthur M.; Khisamutdinova, Ravilya R. (Vestnik of Samara State Technical University Psychological and Pedagogical Sciences, 2023)
The relevance of the problem of the educational potential of the subject training of the future teacher is due to the growing interest in the problem of educating the younger generation. Geopolitical transformations have updated the search for value-semantic regulations of educational work in educational organizations. The aim of the study is to substantiate the educational potential of the subject training of the future teacher in the conditions of modern educational policy. The research methodology is represented by an axiological and activity approach. The main methods used were: comparative analysis of pedagogical and methodological literature, normative legal acts and methodological documents regulating the educational process in educational organizations; generalization and synthesis of the results obtained; questioning and observation. Based on monitoring research data, a portrait of the modern younger generation is presented, as well as characteristics of the “Alpha” generation, that is, children born after 2010 (in accordance with the concept of Mark McCrind). The scientific novelty of the study includes the identified components of the educational potential of the subject training of the future teacher. The value of the study lies in substantiating the educational potential of the subject training of the future teacher in the conditions of modern educational policy. The practical significance of the study is expressed in the presentation of pedagogical developments in the implementation of the educational potential of the subject training of the future teacher using the example of the academic discipline “History of Russia”.